Development of an electrically tuneable Bragg grating filter in polymer optical fibre operating at 1.55 Vm - Kalli, Kyriacos; Dobb, Helen L.; Webb, David J.; Carroll, Karen E.; Themistos, Christos; Komodromos, Michael; Peng, Gangding; Fang, Qi; Boyd, Ian W. (My University, 2007)
We present a thorough study on the development of a polymer optical fibre-based tuneable filter utilizing an intra-core Bragg grating that is electrically tuneable, operating at 1.55 µm. The Bragg grating is made tuneable using a thin-film resistive heater deposited on the surface of the fibre. The polymer fibre was coated via the photochemical deposition of a Pd/Cu metallic layer with the procedure induced by VUV radiation at room temperature. The resulting device, when wavelength tuned via Joule heating, underwent a wavelength shift of 2 nm for a moderate input power of 160 mW, a wavelength to input power coefficient of −13.4 pm mW−1 and time constant of 1.7 s−1. A basic theoretical study verified that for this fibre type one can treat the device as a one-dimensional system. The model was extended to include the effect of input electrical power changes on the refractive index of the fibre and subsequently to changes in the Bragg wavelength of the grating, showing excellent agreement with the experimental measurements.
Keywords: Optical fibre sensors; Fibre Bragg gratings; Polymer optical fibre; Photosensitivity; Wavelength tuning